Identification and Functional Analysis of a Protein Disulfide Isomerase (AtPDI1) in Arabidopsis thaliana - Zhang, Zhengrong; Liu, Xin; Li, Rong; Yuan, Li; Dai, Yaqing; Wang, Xiaoyun (Frontiers in Plant Science, 2018)
Protein disulfide isomerase (PDI) catalyzes the conversion of thiol-disulfide and plays important role in various physiological events in animals. A PDI (OaPDI) from tropical plant was detailed studied and it was found to be involved in response of biotic stress (Gruber et al., 2007). However the activities of PDI related to physiological functions in plants are poorly understood. In the present study, a homologue of human PDI in Arabidopsis (AtPDI1), encoded by the gene (At3g54960), was characterized. The recombinant AtPDI1 protein had disulfide isomerase activity in vitro and two pairs of conservative cysteines in catalytic domains play a crucial role in the protein disulfide isomerase activities. Expression of AtPDI1 in E.coli significantly enhanced stress tolerance of cells and the mutations of critical cysteins almost lose this function. In plants, AtPDI1 was strongly induced by abiotic stresses and exogenous abscisic acid. An Arabidopsis AtPDI1 knock-down mutant (pdi1) and overexpression lines of transgenic plants obtained by this investigation were used to further examine the function of AtPDI1. The mutant line was more sensitive to stresses than the wild-type, while overexpressing AtPDI1 increased tolerance of seedlings to abiotic stresses, with higher germination ratio and longer length of roots than the wild-type. Our results suggested AtPDI1 played roles in anti-stresses in Arabidopsis which related to the activities of protein disulfide isomerase.